2016
DOI: 10.5120/ijca2016908368
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Lung Disease using Local and Global Descriptors

Abstract: Recent trends indicate that instances of chronic respiratory diseases are on the rise in India mainly due to vehicular pollution, air and dust pollution, habit of smoking and also increased population. A World Health Organization report indicates that India has a ranking number one in the world for lung disease deaths. Respiratory diseases like asthma, chronic obstructive pulmonary disease (COPD), Interstitial Lung Disease (ILD), pneumonia, tuberculosis (TB) are emerging as most important health problems in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The classification task carried out with classifier using Histogram of Oriented Gradient (HOG) -global descriptors and Local Binary Pattern (LBP)local descriptors. The prediction performance of the lung disease achieved 98% predictive accuracy [9].…”
Section: Literature Reviewmentioning
confidence: 97%
See 3 more Smart Citations
“…The classification task carried out with classifier using Histogram of Oriented Gradient (HOG) -global descriptors and Local Binary Pattern (LBP)local descriptors. The prediction performance of the lung disease achieved 98% predictive accuracy [9].…”
Section: Literature Reviewmentioning
confidence: 97%
“…The HOG detector depends on the window overlap principle by default, the HOG blocks typically overlap such that each cell contributes more than once to the final feature descriptor. Adjacent neighboring blocks are overlapping by eight pixels both horizontally and vertically [9,10,19].…”
Section: Step4: Block Overlappingmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of asthma is at a higher rate in elderly men living in urban areas as compared to elderly women and rural areas. Many studies showed that stress can also worsen asthma [25,26]. Heart diseases include heart attack, stroke, cardiac arrest, high blood pressure, peripheral artery disease, cardiovascular condition, and heart failure.…”
Section: Major Chronic Ailments Among Eldersmentioning
confidence: 99%